INVESTIGATING THE COLLOCATION OF THE WORDS 'MOM' AND 'DAD' IN ALEC GREVEN'S NOVELS: A CORPUS LINGUISTIC ANALYSIS OF SEMANTIC PREFERENCES AND PROSODY - Zuraida, Ida; Simatupang, Ervina CM (University of Kuningan, 2023)
This research delves into the collocation and semantic analysis of the words